The impact of using a multimedia learning tool on mechanical engineering students' creativity - Hafizoah, Kassim (2011)
This research examines the impact of utilising multimedia learning tool(MLT)on engineering students' ability to think creatively and make creative engineering products.This research links multimedia learning to creativity by looking at how to manage cognitive load on the cognitive system for effective information processing and knowledge construction. Theoretical perspectives include Cognitive Load Theory (Sweller et al., 1998),Cognitive Theories of Multimedia Learning (Mayer, 2009) and creativity theories (Runco & Chand, 1995; Wallas, 1926).The influences of moderating variables such as students'diversity,environmental factors and emotional effects were also explored.This research used a mixed method approach with a pre-test post-test quasiexperimental design as the predominant data gathering method.The Torrance Tests for Creative Thinking (TTCT) and the Creative Product Semantic Scale (CPSS) were used This study extends previous research by including in its outcomes, the use of established creative performance measurements.Other research instruments used included a student questionnaire,observation and semi-structured interviews.